2017
DOI: 10.1093/toxsci/kfx151
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Pulmonary Vascular Thrombosis in Rats Exposed to Inhaled Sulfur Mustard

Abstract: Sulfur mustard (SM) is a chemical warfare agent. When inhaled, SM causes significant injury to the respiratory tract. Although the mechanism involved in acute airway injury after SM inhalation has been well described previously, the mechanism of SM's contribution to distal lung vascular injury is not well understood. We hypothesized that acute inhalation of vaporized SM causes activated systemic coagulation with subsequent pulmonary vascular thrombi formation after SM inhalation exposure. Sprague Dawley rats i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The current study is novel in its use of the coculture model of primary HAECs and primary human endothelial cells exposed to pure NM vapor. This in vitro coculture system was developed to model the known in vivo pulmonary complications of high-concentration mustard vapor exposure with AEC death, 7,8 adjacent pulmonary vasculature injury, 11,15,17 and subsequent vascular leak. 16 Different from prior in vitro mustard exposure studies, 18,[23][24][25][26] the model system uses vaporized NM in place of topical mustard exposure for exposures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study is novel in its use of the coculture model of primary HAECs and primary human endothelial cells exposed to pure NM vapor. This in vitro coculture system was developed to model the known in vivo pulmonary complications of high-concentration mustard vapor exposure with AEC death, 7,8 adjacent pulmonary vasculature injury, 11,15,17 and subsequent vascular leak. 16 Different from prior in vitro mustard exposure studies, 18,[23][24][25][26] the model system uses vaporized NM in place of topical mustard exposure for exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Following high-dose mustard inhalation exposure, doi: 10.1111/nyas.14367 injury to both the airway epithelial and adjacent endothelial cell layers occurs. 15 This acute airway injury results in bronchial vascular leak and subsequent bronchial cast formation. 11,16,17 Fibrin-rich bronchial casts cause significant airway obstruction, and ultimately, death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 , 7 , 13 ] Studies have shown that the effect of multiple growth factors is better than that of single growth factor, which may be related to a variety of factors, which are related to multiple stages of the healing process. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Both nebulized and direct instillation of t‐PA into the airways via bronchoscopy have been used off‐label to treat fibrin airway casts 61 . In a lethal animal model of both severe pulmonary microvascular thrombi and severe bronchial fibrin casts, treatment with airway t‐PA resulted in improved survival, dissolved airway casts, and normalized pO 2 and pCO 2 62,63 . However, the mounting evidence specific to COVID‐19 that shows pulmonary microvascular thrombosis as a predominant finding 26–28 combined with normal lung compliance and high alveolar‐arterial oxygen gradients 64 suggests intravascular delivery may be the more appropriate delivery route, with concern that intra‐airway delivery via intratracheal instillation or nebulized solutions may increase the risk to health care workers by exposing them to infectious airway secretions.…”
Section: Fibrinolysis Ards and The Possible Role Of Fibrinolytic Thmentioning
confidence: 99%